PENGARUH LIKUIDITAS, SOLVABILITAS DAN AUDIT EFFORT TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Reni, Sonia; Hardi, Hardi; Meilda, Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine and analyze again about (1) the effect of Liquidity on Audit Report Lag, (2) the effect of Solvability on Audit Report Lag, (3) the effect of Audit Effort on Audit Report lag. The population of this study are mining sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period with a total of 47 companies. The sample used in this study were 35 companies with a total data of 105 companies' financial statements in 3 consecutive years. The sampling technique was carried out using a purposive sampling method. The method of data analysis in this study is to use (Statistical Package for the Social Sciences) using SPSS Software version 25.0. The results showed that liquidity has an effect on audit report lag, solvency has an effect on audit report lag, and audit effort has an effect on audit report lag. So, the conclusion of this study is that all hypotheses are accepted. Keywords: Liquidity, Solvability, Audit Effort, Audit Report la